PELATIHAN PEMBUATAN NATA DE CASSAVA DALAM UPAYA PENINGKATAN KEBERDAYAAN INDUSTRI KERUPUK SINGKONG - Wahyudi, Bayu; Hastarina, Merisha; Idealistuti, Idealistuti; Auladi, Syafaat; Habieby, Nabil (Universitas katolik Musi Charitas, 2025)
Purpose: This community service project aims to improve the productivity and sustainability of cassava cracker small industries by introducing appropriate technology for processing cassava pulp wastewater into nata de cassava. The program addresses key challenges faced by producers, including inefficient processing methods and the absence of effective waste management practices that contribute to environmental pollution. Design Methodology Approach: The program was implemented through a participatory approach consisting of field observation, group discussions, technology socialization, and hands on training. Appropriate production equipment, including a cassava grating machine and a hydraulic press, was introduced. In addition, technical training was provided on liquid waste processing through a fermentation method using Symbiotic Culture of Bacteria and Yeast to produce nata de cassava. Findings: The results indicate an improvement in partners’ knowledge and technical skills related to waste utilization and production efficiency. The introduction of new equipment enhanced the effectiveness of cassava processing, while nata de cassava production training enabled the transformation of liquid waste into an alternative product with economic value. Practical Implications: The implementation of simple and appropriate technology supports cleaner production processes, reduces environmental impact, and creates new income opportunities for small scale cassava based industries. The approach demonstrates practical solutions for improving business resilience and sustainability. Originality Value: This project integrates circular economy principles through waste to product innovation within community based enterprises. It offers a replicable model for sustainable rural industry development by combining technological assistance, capacity building, and environmental responsibility.